IBN SINА AND HIS CONTRIBUTION TO SPIRITUAL AND MORAL EDUCATION: RETHINKING THE HERITAGE OF EASTERN THINKERS - Khalilova, Shakhlo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article examines the relevance of spiritual and moral education in modern society, especially in conditions of moral crisis and geopolitical problems. The author emphasizes the importance of a harmonious combination of national and universal values in creating a new model of the educational process. Special attention is paid to the study of the heritage of thinkers of the past, in particular, the contribution of Ibn Sina, an outstanding thinker of the East. Ibn Sina presented education as a complex process, including mental, physical, aesthetic and moral development. His ethical ideas, especially in the field of morality and friendship, can be valuable for modern teachers and specialists in the field of spiritual and moral education. The article calls for rethinking and using the heritage of Eastern thinkers in the process of raising children and adolescents, as well as in the professional training of future teachers.